REVITALISASI LEMBAGA PENDIDIKAN DALAM UPAYA MEMBANGUN KARAKTER BANGSA - Harum Natasha (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
Education in Indonesia is having a great challenging. It cannot be denied that nation moral degradation today is related to our education system and institution. Start from corruption happened in almost all government institution, nepotism in recrutment as well ass collution in every policy and development program arrangement has been unconsciously the root grown and developed forming nation character. In addition, within the global problems which have positive and negative impact toward Indonesian life. It needs intelectual ability and emotional maturity to maximize the positive impact from the globalization itself such as the opening of working opportunity based on society and nation needs. To minimize the negative impact such as the changing of norm and the value of life which oftenly be contradictive with the norm and the value of life in society, including indicator and nation character changing. The success of education with character is really defined by the institution with character. It should be reflected from the teacher/lecturer character, education leader and education institution environtment. The empowerment of education institution aparatus especially the education leader as well as teacher and lecturer by giving opprotunity to function and dinamize the implementation of nation philosophy into integrated and sustainable education institution. Revitalisation at this point related to the selection of education institution on teachers employement so that the quality standard used on this would not be low. Therefore, in the future could share the success to build education with character which is able to touch all way, level, and types of education in this nation.